Ocular manifestation of systemic tuberculosis in children at tertiary pediatric hospital in North India - Meenakshi Wadhwani; Amit Kumar; Dhulika Dhingra; Hem Sati (Kerala Journal of Ophthalmology)
Background: Tubnerculosis is Characterised by the presence of granuloma formation. The mode of spread of pulmonary tuberculosis is via airborne aerosol. This bacteria enters the lungs and leads to latent infection in susceptible hosts. Diagnosis is mostly presumptive in ocular tuberculosis. There is lack of uniform diagnostic criteria. Despite of vast developments in diagnostic tools, evidence of systemic tuberculosis disease along with suggestive clinical ocular findings is considered the major diagnostic criterion for ocular tuberculosis. Aim: This study aims to evaluate ocular findings in diagnosed cases of pulmonary and extrapulmonary tuberculosis in children. Methods: The study included children with various type of pulmonary and extra pulmonary tuberculosis. All these children referred to ophthalmology department to rule out ocular manifestations were evaluated on the basis of visual acuity, anterior segment and dilated posterior segment examination. Results: A total of 90 children were diagnosed with tuberculosis, of whom 30 (33.3%) were male and 60 (66.7%) were female, The mean age of presentation is 4±7 years. 30 (33.7 %) were a diagnosed case of pulmonary kochs, 52 (58.4 %) had tubercular meningitis (TBM), remaining 7 (7.8%) had other extrapulmonary kochs. The most common anterior segment finding was lateral rectus palsy in 14 (15.5%) children, the most common posterior segment finding was papilledema in 20 (22.2%) children. Conclusion: Tuberculosis is one of those pandemic in the world that can affect each and every organ of the body. A timely diagnosis of ocular findings can prevent these children from permanent ocular morbidity and blindness.